Effect of Persuasion on Information Diffusion in Social Networks - Das, Abhimanyu; Gollapudi, Sreenivas; Kiciman, Emre (2014)
One of the key factors guiding the act of communication between individuals in a social network is the desire to persuade or inﬂuence one another. In this paper, we study the interplay between a person writing (selecting) a message to send to another and the effect that the message has on its recipient. Using large-scale online user studies, we focus on a single effect (persuading or changing a recipient’s opinion about a topic) and its relationship to various measurable properties of the written message often associated with persuasive techniques, namely the degree of emotional and logical content. We ﬁnd that the persuasive efﬁcacy of these properties varies by domain of discussion and by individual susceptibility, and that senders appear to strategically select their persuasion techniques. Based on these results, we develop a structural model of information diffusion and show through simulations that the emergent larger-scale behaviors are consistent with current models of information cascades and, moreover, are able to model as yet unexplained empirically observed variance in the structural virality of cascades.